2015
DOI: 10.1121/1.4919317
|View full text |Cite
|
Sign up to set email alerts
|

Expectations and speech intelligibility

Abstract: Socio-indexical cues and paralinguistic information are often beneficial to speech processing as this information assists listeners in parsing the speech stream. Associations that particular populations speak in a certain speech style can, however, make it such that socio-indexical cues have a cost. In this study, native speakers of Canadian English who identify as Chinese Canadian and White Canadian read sentences that were presented to listeners in noise. Half of the sentences were presented with a visual-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
129
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(170 citation statements)
references
References 53 publications
12
129
6
1
Order By: Relevance
“…Consistent with this bias, when listeners were asked to judge the veracity of statements of sentences spoken by talkers with a variety of accents, including a native accent, they rated the statements spoken by the native talkers as being more truthful than the statements spoken by the talkers with foreign accents (Lev-Ari and Keysar, 2010). Suggesting that these biases against non-native talkers may also impact the accuracy of speech perception, Babel and Russell (2015) found that though both accentedness ratings and speech perception could be shifted by leading listeners to believe speech was produced by an Asian vs a White talker.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Consistent with this bias, when listeners were asked to judge the veracity of statements of sentences spoken by talkers with a variety of accents, including a native accent, they rated the statements spoken by the native talkers as being more truthful than the statements spoken by the talkers with foreign accents (Lev-Ari and Keysar, 2010). Suggesting that these biases against non-native talkers may also impact the accuracy of speech perception, Babel and Russell (2015) found that though both accentedness ratings and speech perception could be shifted by leading listeners to believe speech was produced by an Asian vs a White talker.…”
Section: Introductionmentioning
confidence: 89%
“…Future work will be needed to link listeners' perceptions of the talkers to listeners' perceptions of the given accents and then determine the extent to which listener attitudes regarding the talker account for variance perceiving speech beyond attitudes toward the accent. Listeners' judgments regarding the strength of foreign accent are not related to their ability to perceive accented speech (e.g., Babel and Russell, 2015;Munro and Derwing, 1995), but it remains to be seen if their attitudes regarding foreign accents, and how they relate to attitudes toward foreign-accented talkers, impacts accented speech perception. Another possibility is the extent to which listeners have experience listening to a given accent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a vowel-matching task, listeners selected different tokens as being most similar to the one produced by the speaker depending on whether they believed the speaker to be from Detroit or Canada (Niedzielski 1999). More strikingly, listeners found the speech of native English speakers to be more foreign-accented (Babel and Russell 2015;Rubin 1992) and less intelligible (Babel & Russell) when it was presented with a picture of an Asian versus a Caucasian speaker.…”
Section: The Role Of Input In Shaping Expectationsmentioning
confidence: 99%
“…Thus, listeners are better at understanding Chinese-accented English embedded in noise if they expect the speaker to be a native speaker of Chinese than if they expect the speaker to be a native speaker of English (McGowan, 2015), and conversely, they are better at understanding native speech when they do not expect a foreign accent (Babel and Russell, 2015).…”
Section: Introductionmentioning
confidence: 99%